ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA BERDAMPAK KEPADA KINERJA KARYAWAN DI STMA TRISAKTI - Sidik, Syahrial; Tejamirah, Oties (P3M Trisakti School of Insurance (TSI), 2022)
This study aims to determine the effect of compensation, work motivation, compensation on employee performance, motivation on employee performance and to determine the effect of job satisfaction on employee performance at Trisakti School of Insurance (TSI). This study uses a saturated sample by using all employees as many as 35 respondents at TSI. Data collection techniques using questionnaires and literature study. This research uses quantitative analysis with validity, reliability, correlation coefficient, determination coefficient, t test, F test, path analysis and Sobel analysis to test the effect of intervening variables. Based on the results of the study, it shows that compensation and motivation partially have a positive and significant effect on job satisfaction, compensation and motivation partially have a positive and not significant effect on employee performance, job satisfaction has a positive and insignificant effect on employee performance, job satisfaction mediates compensation has a positive and significant effect on employee performance. significant effect on employee performance, and job satisfaction mediating motivation has a positive and not significant effect on employee performance. The advice given in order to improve employee performance is to consider employee input regarding the policy on the amount of basic salary that must be adjusted to the employee's work ability, as well as determining the amount of individual achievement incentives. To increase work motivation, it is necessary to apply a sense of openness between employees and high school leaders and establish brotherly relationships between each employee, and it is necessary to hold periodic training to improve the ability of employees to provide services so that it will affect employee job satisfaction which in turn affects employee performance.